2018
DOI: 10.1111/twec.12674
|View full text |Cite
|
Sign up to set email alerts
|

On the exposure of the BRIC countries to global economic shocks

Abstract: The financial crisis led to a deep recession in many industrial countries. While large emerging countries recovered relatively quickly, their performance deteriorated in recent years, despite the modest recovery in advanced economies. The higher divergence of business cycles is closely linked to the Chinese economy. During the crisis, the Chinese fiscal stimulus prevented an abrupt decline in GDP growth not only in that country, but also in resource‐rich economies. Due to lower commodity demand, the environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Moreover, we use established methods to concentrate the GDP growth dynamics of the trading partner countries in a single GDP measure, and hence, our approach is not restricted to the estimation of bilateral models (in the sense of two‐country VAR models.) We are also confident that our estimations are able to mirror the underlying economic relationships as we are able to reproduce main features of related studies (see Belke et al., 2018; Erten, 2012; Utlaut & van Roye, 2010).…”
Section: Literature Reviewsupporting
confidence: 70%
See 3 more Smart Citations
“…Moreover, we use established methods to concentrate the GDP growth dynamics of the trading partner countries in a single GDP measure, and hence, our approach is not restricted to the estimation of bilateral models (in the sense of two‐country VAR models.) We are also confident that our estimations are able to mirror the underlying economic relationships as we are able to reproduce main features of related studies (see Belke et al., 2018; Erten, 2012; Utlaut & van Roye, 2010).…”
Section: Literature Reviewsupporting
confidence: 70%
“…The fast integration of China and the other BRIC countries in the world economy since the 1990s has been facilitated by favorable global economic circumstances: Strong foreign demand supported by trade liberalizations, such as for instance China's WTO entry in 2001, decreasing global interest rates and increases in commodity prices (Belke et al., 2018; Cubeddu et al, 2014). From the early 1990s until the financial crisis China's share of the world economy has more than doubled (see Figure in the Online Appendix) 1…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…China and other resource-rich economies prevented the abrupt decline in GDP but the situation turned more challenging lately. The findings for individual BRICS economies indicated that China has significant influence on other economies; the spill over effects from China are more significant for natural resource rich economies (Belke et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 98%